TECHNICAL ASPECTS OF LAPAROSCOPIC SLEEVE GASTRECTOMY - RAMOS,Almino Cardoso (2015)
Background : The vertical gastrectomy indications for surgical treatment of morbid obesity have increased worldwide. Despite this increase, many aspects of surgical technique still remains in controversy. Aim : To contribute presenting surgical details in order to better realize the vertical gastrectomy technique in bariatric surgery. Methods : Technical systematization, patient preparation, positioning of the trocars, operative technique and postoperative care are presented in details. Results : During 12 months were enrolled 120 patients undergoing GV according to the technique described herein. The results are published in another ABCD article (ABCD 2015;28(Supl.1):61-64) in this same volume and number. Conclusion : The surgical technique proposed here presented itself viable and facilitating the surgeon's work on difficult points of the vertical gastrectomy.